Inflamação no tecido adiposo visceral em ratas ovariectomizadas : efeitos do treinamento resistido e da reposição de estrogêni - Rodrigues, Maria Fernanda Cury (2016)
The ovariectomy associated with decreased estrogen is associated with increased prevalence of obesity, a condition that increases the risk of metabolic syndrome. Evidence shows that inflammation-induced obesity in visceral adipose tissue (VAT) promotes deregulation in the expression of inflammatory cytokines. Hormone replacement (HR) and resistance training (RT) have beneficial effects on postmenopausal women, but it is unclear whether these interventions are effective in minimizing inflammation in VAT. The aim of this study was to evaluate the effects of RT and ER in adipocyte size, gene expression and protein concentration of inflammatory markers. Rats Sprague-Dowley females were divided into six groups: Sham-Sedentary (Sham-Sed), Ovariectomized Sedentary (Ovx-Sed), Sham-Trained (Sham-TR), Ovx-TR, Ovx-Sed-ER and Ovx-TR-ER. The ER was performed using Silastic® capsules. During the 12- week RT, the animals climbed a ladder with weights attached to the tails. The morphology was confirmed by histological analysis. The gene expression was performed by RT-PCR and protein concentration by Multiplex / Luminex assays. Ovariectomy increased adipocyte size and decreased expression of anti-inflammatory molecules in TAV, which was partially restored by RE. In turn, TR, was able to minimize the increase in inflammation in TAV of Ovx rats. We conclude that ER and TR were effective in alleviating inflammation promoted by Ovx in TAV.